PENGARUH PERHATIAN ORANG TUA DAN SIKAP SOSIAL TERHADAP PRESTASI BELAJAR IPS SISWA KELAS V SEKOLAH DASAR - Suryanti dan Samsi Haryanto (Universitas PGRI Yogyakarta, 2014)
This study aims to determine whether there is influence of parental concern and social attitudes to learning achievement Social Sciences Elementary School fifth grade students. The population in this study were fifth grade students of elementary school of 60 students, while the sample of 50 students (5% of the total population) is determined by purposive random sampling technique according to the size of the sample with 5% significance level. Based on the results of this study concluded that: The first hypothesis reads: